147 Post challenge hyperglycaemia: a predictor of poor cardiovascular outcome in patients with ACS. (16th May 2012) - George, A; Chattopadhyay, S; John, J; Beer, S
Abstract : Background: Patients with elevated random or diabetes have been known to have an adverse outcome following acute coronary syndrome (ACS). Most centers use fasting blood glucose to assess the glycaemic status for these patients, however the effect of elevated 2 h-post challenge BG to either diabetic or pre-diabetic levels on adverse cardiovascular events after myocardial infarction has been inadequately explored. Objective: We aim to assess the glucometabolic states of patients presenting with ACS using OGTT, and its the long term prognostic implications. Methods and Results: All patients admitted to the coronary care unit, with ACS to our hospital between November 2005 and October 2008 were included. All patients with known history of diabetes were excluded. All patients underwent an oral glucose tolerance test (OGTT) with 3–5 days after admission. The incidence of all cause mortality, cardiovascular death, re-infarction, CCF and CVA were collected. The primary end point was incidence of cardiovascular mortality, non-fatal reinfarction, CCF and non-haemorrhagic stroke. 930 patients were admitted in the described period with ACS, of which 136 were diabetic and noted were not available for 26, leaving 768 patients in the study. 337 (44%) had normal glucose tolerance, while 279 (36%) had impaired glucose tolerance and 152 (20%) had newly detected diabetes. The outcome of MACE are described in Abstract 147 table 1 . The analysis shows a significantly higher incidence (p<0.05, HR 1.56, CI 1.15 to 2.13) of adverse cardiovascular outcome in patients with impaired glucose tolerance as well as diabetes (post challenge hyperglycaemia). Conclusion: The study concludes that a significant proportion of patients who present with ACS have abnormal glucose tolerance. Patients with abnormal glucose tolerance have significantly higher incidence of adverse cardiovascular outcome.